2012
DOI: 10.1016/j.bbamem.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of the transmembrane C domain of the mannitol permease from Escherichia coli using 5-FTrp fluorescence spectroscopy

Abstract: The mannitol transporter EII(mtl) from Escherichia coli is responsible for the uptake of mannitol over the inner membrane and its concomitant phosphorylation. EII(mtl) is functional as a dimer and its membrane-embedded C domain, IIC(mtl), harbors one high affinity mannitol binding site. To characterize this domain in more detail the microenvironments of thirteen residue positions were explored by 5-fluorotryptophan (5-FTrp) fluorescence spectroscopy. Because of the simpler photophysics of 5-FTrp compared to Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The finding that B. methanolicus MGA3 is able to catabolize low arabitol concentrations effectively ( K S value of about 3 mM) is in line with our prediction that arabitol is taken up by the cells via arabitol PTS encoded by arabitol inducible genes atlABC . High substrate affinity has been reported in several organisms in relation to PTS-mediated uptake (Nothaft et al, 2003; Lindner et al, 2011; Opačić et al, 2012), as is also the case for mannitol in B. methanolicus : the K S value for mannitol was determined to be 0.2 ± 0.1 mM with genes mtlF, mtlA , and mtlD known to code for a mannitol-specific PTS enzyme IIA component, a mannitol-specific PTS enzyme IIBC component and a mannitol-1-phosphate 5-dehydrogenase, respectively (Heggeset et al, 2012; Irla et al, 2016). However, the observed growth rates and substrate uptake rates were higher for mannitol than for arabitol, and the biomass yield for the C5 sugar alcohol arabitol was lower than for the C6 sugar alcohol mannitol (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that B. methanolicus MGA3 is able to catabolize low arabitol concentrations effectively ( K S value of about 3 mM) is in line with our prediction that arabitol is taken up by the cells via arabitol PTS encoded by arabitol inducible genes atlABC . High substrate affinity has been reported in several organisms in relation to PTS-mediated uptake (Nothaft et al, 2003; Lindner et al, 2011; Opačić et al, 2012), as is also the case for mannitol in B. methanolicus : the K S value for mannitol was determined to be 0.2 ± 0.1 mM with genes mtlF, mtlA , and mtlD known to code for a mannitol-specific PTS enzyme IIA component, a mannitol-specific PTS enzyme IIBC component and a mannitol-1-phosphate 5-dehydrogenase, respectively (Heggeset et al, 2012; Irla et al, 2016). However, the observed growth rates and substrate uptake rates were higher for mannitol than for arabitol, and the biomass yield for the C5 sugar alcohol arabitol was lower than for the C6 sugar alcohol mannitol (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no evidence of cooperativity in the bcChbC dimer; however, given that the cytoplasmic gate appears to be supplied by the opposing protomer, it is possible that this could provide a mechanism for cooperativity, as sugar exiting the cavity of one protomer could be sensed by the other. Furthermore, residues in the N-terminal half of MtlA (the region corresponding from TM1 to TM4 in bcCHBC) were shown to be in close contact with mannitol, the sugar was shown to be located closer to the periplasm, and substantial differences were observed between solvent exposed residues in MtlA and their expected counterparts in the bcChbc structure[69, 70]. Tryptophan phosphorescence spectroscopy indicated that F97 in MtlA (a predicted cytoplasmic loop residue that overlays TM3 in bcChbC) is part of a β-sheet fold[71].…”
Section: Transportmentioning
confidence: 99%
“…Satisfactory results from the models using EEM fluorescence data, for the E. coli and K. pneumoniae bacteria, demonstrate the sensitivity of the technique in detecting variations in the nuclear content of the cells and in the structure of the membranes itself. As reported by Opačić et al 19 , who used fluorescence spectroscopy on structural investigation of the transmembrane C domain of the mannitol permease from Escherichia coli, the results showed that the technique was capable to differentiated the structure of EII mtl from structure of a IIC protein transporting diacetylchitobiose. Additionally, Romantsov et.…”
Section: Resultsmentioning
confidence: 73%
“…As reported by Opačić et al . 19 , who used fluorescence spectroscopy on structural investigation of the transmembrane C domain of the mannitol permease from Escherichia coli , the results showed that the technique was capable to differentiated the structure of EII mtl from structure of a IIC protein transporting diacetylchitobiose. Additionally, Romantsov et.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation